Fostering Women's Economic Empowerment through Special Economic Zones : Comparative Analysis of Eight Countries and Implications for Governments, Zone Authorities and Businesses - World Bank; International Finance Corporation (World Bank, Washington, DC, 2017)
This global report examines the opportunity for special economic zones to promote women's economic empowerment and boost zone and enterprise competitiveness in developing countries. The research covers Bangladesh, China, Costa Rica, Egypt, El Salvador, Jordan, Kenya, and the Philippines. The study focuses on women's economic empowerment in the context of zones at three levels: (i) fair employment and working conditions for female employees; (ii) equal access to opportunities for professional advancement; and (iii) investment opportunities for female entrepreneurs. The study also examines gender-friendly policies and practices that support these three main goals, which include a wide range of options around laws, regulations, labor policies, gender-sensitive professional development programs, family support mechanisms, women's health programs, and supplier diversity and capacity-building initiatives. This study establishes the business case for investments in women's economic empowerment in SEZs, and identifies good-practice examples of recommended enablers to address this investment opportunity. Enablers are defined as efforts to counteract the negative impact of the obstacles women face in economic participation, and can include policies and programs at the government, zone, and enterprise level. The study provides background, evidence of challenges and success stories, comprehensive recommendations, and a suite of tools and tips to implement the recommendations successfully.